Usefulness of laparoscopy in the management of incidentally discovered retroperitoneal liposarcoma mimicking inguinal hernia: A case report and literature review. (2020) - Matsumoto, Takashi; Mima, Kosuke; Ono, Asuka; Miyanari, Nobutomo; Morito, Atsushi; Yumoto, Shinsei; Kosumi, Keisuke; Inoue, Mitsuhiro; Mizumto, Takao; Kubota, Tatsuo; Baba, Hideo
Highlights: We present a rare case of retroperitoneal liposarcoma with an inguinal swelling, which was diagnosed after laparoscopic surgery for inguinal hernia. It is necessary to consider a possibility of enlargement of retroperitoneal liposarcoma and perform CT or MRI of the abdomen and pelvis in cases of irreducible inguinal swelling of retroperitoneal fatty tissue. Abstract: Introduction: Liposarcomas comprise around 10%–16% of soft tissue sarcomas. The two major sites of liposarcoma are the extremities and retroperitoneum. However, retroperitoneal liposarcomas mimicking inguinal hernia are rare. We present a case of retroperitoneal liposarcoma mimicking inguinal hernia, which was diagnosed after laparoscopic surgery and underwent curative resection. Presentation of case: A 46-year-old man was admitted to our hospital with a right inguinal pain and swelling that had been recognized for 3 years. We diagnosed the inguinal swelling as a right inguinal hernia and planned laparoscopic surgery for inguinal hernia repair. A hernia sac, however, was not found and swollen retroperitoneal fatty tissue near the right internal inguinal ring was observed by laparoscopy. We aborted the surgical procedure and performed computed tomography and magnetic resonance imaging, which revealed an extraperitoneal and lipomatous tumor extending through the inguinal canal to the scrotum. Wide local excision of the tumor, along with right orchidectomy, was performed under laparotomy. Histopathological diagnosis showed well-differentiated liposarcoma of the retroperitoneum and confirmed tumor-free margins. No evidence of recurrence or metastasis was seen in the 9 months after curative resection. Discussion and conclusion: Laparoscopic surgery for inguinal hernia enables to observation of the inguinal region and management of rare cases, such as retroperitoneal liposarcoma.